The Effect of Engineering Design-Based STEM Activities on Students' Entrepreneurial Skills (Journal of Science Learning, 2026)
The aim of this study is to reveal the effect of engineering design-based STEM activities on the entrepreneurial skills of seventh-grade students. In this context, students were asked to design engineering design-based STEM activities for problems identified using real-life situations, and at the end of this process, an attempt was made to determine whether their entrepreneurial skills had changed based on the solutions they brought to the problem. The research was conducted using a mixed method and a sequential design, first obtaining quantitative data and then collecting and analysing qualitative data to examine the reasons behind the results obtained from the quantitative data in depth. The participants of the research consisted of 50 seventh-grade students, 26 in the experimental group and 24 in the control group, attending a state secondary school. The data collection tools used in the study were the science-based entrepreneurship scale and a semi-structured interview form. The results of the study revealed that engineering design-based STEM activities had a positive effect on the development and improvement of entrepreneurial skills in students. The participants stated that they enjoyed the application process, were active during the process, and that a student-centred process was effective in achieving these results. The participants emphasised that it was a process that developed their entrepreneurial skills and changed their perceptions of entrepreneurship.